PRARANCANGAN PABRIK ETIL SILIKAT-40 DARI ETANOL DAN SILIKON TETRAKLORIDA DENGAN KAPASITAS 50.000 TON/TAHUN - , SEPTIAN ARIEF NUR RAHMAN, Indra Perdana, S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Ethyl Silicate-40 is a compound that is widely used in semiconductor industries to produce microchips, as a anti-corrosive coating material, and binding agent. Ethyl silicate also can be used as raw material for specialties material like aerogel. Development opportunities for ethyl silicate industry in Indonesia is quite large, considering that there is no manufacturing plant has been established in Indonesia. The plant is planned to operate 330 days a year with installed ethyl silicate production capacity of 50.000 tons/year. Side product is HCl 37% solution whiches produced 129.688,69 tons/year. The main raw material required is 53.076,92 tons/year of ethanol 96%, and silicon tetrachloride 51.081,73 tons/year. Method for ethyl silicate production is Von Ebelmanâs Method. In general, ethyl silicate production stage processes are as follows: (i) reaction between ethanol and SiCl4 in a continuous stirred tank reactor, (ii) absorbtion of side product HCl gas by water and purification into HCl 37% solution, (iii) purifying ethyl silicate product by distillation process. Utility plant unit supplies the cooling water as much as 9,848 tons/hour, 1141,885 kW electricity, compressed air up to 168m3/jam and 1,8083 tons/hour steam. The plant will be established in the Gresik region. East Java, with raw material oriented consideration. Gresik region close to ethanol industry, and close to the seaport making it easier to procure raw material silicon tetracloride imported from China, as well as marketing and delivering product ethyl silicate. The overall employee are 187 with total plant area of 54.000 square meter. Calculation of economic evaluation give results: the fixed capital required is $16.653.615,24 + Rp.294.497.926.548,46, and working capital is $32.159.610,41 + Rp.13.099.401.008,49. At full production rate, obtained ROI before tax is 24,38 %, ROI after tax is 12,19%. POT before tax 2,91 years, POT after tax 4,51 years, wtih BEP at 50,82 % capacity, SDP at 24,59 % capacity, and 19,60 % of DCFRR. Based on consideration of the economic evaluation results, the ethyl silicate-40 plant with 50.000 tons/year of capacity is worth to be studied further.